The SAGE handbook of social media research methods - Quan-Haase, Anabel; Sloan, Luke (SAGE reference, 2022)
The SAGE Handbook of Social Media Research Methods offers a step-by-step guide to overcoming the challenges inherent in research projects that deal with 'big and broad data,' from the formulation of research questions to the interpretation of findings. The Handbook includes chapters on specific social media platforms such as Twitter, Sina Weibo and Instragram, as well as a series of critical chapters" -- Back cover.